KUALITAS KEHIDUPAN KERJA, SELF EFFICACY, DAN KINERJA KARYAWAN: EFEK MEDIASI MOTIVASI KERJA - Kusnoto Kusnoto; Tigor Sitorus (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2016)
This research is driven by the phenomenon and the difference of research result about thecorrelation relationship between Quality Work of Life and Self efficacy with EmployeePerformance, therefore the researcher tries to fill the research gap by proposing WorkMotivation as a mediating variable, where research with survey method conducted on 180employees PT. Bank BRI Branch BSD. Analyze research by using model of structural equationwith results; 1). Quality work of life has a significant negative effect on employee performance,2). Quality work of life has a significant positive effect on work motivation, 3). Self efficacy hasa significant positive effect on the performance of the karawan, 4). Self efficacy has asignificant positive effect on work motivation, 5). Motivation of work has a significant positiveeffect on employee performance, so this finding proves that work motivation acts as a perfectmediator of Quality Work of Life with Employee Performance.